Role of Women in Telangana Statehood Movement from South India: Contributions and Case Story of Belli Lalitha. Issue 1 (June 2020) - Gangadhar, Bongurala
The role of women in Telangana statehood movement has immense importance and has paved a way for the realization of the dreams of women who aspired for emancipation from human trafficking, dowry, domestic violence and liquor mafia. The role of Belli Lalitha in the 1990s sparked a wave of movement with her folk songs to mobilize people to demand their rights. Belli Lalitha's journey started with ups and downs as a school dropout, married early, labourer in a cotton mill, labour activist, folk singer and political leader, but her sudden murder by the goons and political leaders changed the pace of the movement from peak level to ground. To mobilize millions of people in the final phase of the Telangana movement, the folk song tradition familiarized at grass-root level by Belli Lalitha occupies an important position.